Clinical and surgical diagnostic evidence in subscapularis tendon injuries - Lagorio, Matteo; Fidanza, Andrea; Fardetti, Francesco; Raglione, Vincenzo; Beccarini, Alessandro; Calvisi, Vittorio (Lo Scalpello - Journal, 2022)
Objective. The purpose of the present study was to estimate the diagnostic accuracy of a spectrum of physical examination tests, explaining how to perform them and compare them with arthroscopic findings to identify which have the best ability to accurately detect a subscapularis tear in a population of primary care patients with shoulder pain. Methods. Three established clinical tests were evaluated in 56 consecutive patients prior to shoulder arthroscopy. The tests included the Lift Off test, Napoleon test, and Bear Hug test. The integrity or not of the subscapularis tendon at surgery was considered as the gold standard. Lesions to the subscapularis were graded according to Lafosse.Results. Among the 56 patients there were 17 with arthroscopic diagnosis of subscapularis lesions accounting for an incidence of 30%. The sensitivity for subscapularis tears for the Lift-off test, Napoleon test, and Bear Hug test was 80.15, 58.82, and 82.35%, respectively. Specificity was 54.55, 56.82, and 55.56%, respectively. A significant correlation was found between arthroscopic findings and physical examination only for the Bear Hug. Conclusions. In the present study, the Bear Hug test was found to have the highest sensitivity of all tests studied. Nevertheless, it appears advisable to perform more than one clinical test to further improve the clinical ability to detect subscapularis tears.